Técnicas de difração de elétrons e de caracterizações elétricas e térmicas combinadas para análise de transformações de simetria em estruturas perovskitas distorcidas : caso das soluções sólidas (Pb1-xCax)TiO3 - Estrada, Flávia Regina (Universidade Federal de São Carlos, 2017)
The main objective of this work was the unequivocally determination of the crystal symmetry of distorted perovskite structure by direct and indirect methods, with the solid solution system Pb1-xCaxTiO3 (PCT) as the case study. Therefore, ferroelectric ceramic of PCT were investigated using electron diffraction techniques, electric characterization and thermal expansion measurements at compounds with controversial results in the literature about its crystallographic symmetries and polar states, mainly in the Morphotropic Phase Boundary (MPB). Qualitative analysis of synchrotron X-ray diffraction pattern from PCT powders confirms that the octahedral tilting distortions exist from the calcium concentration x = 0.40. From this result, based on subgroup relations analysis and considering only the point group 2mm as a maximal subgroup (as a suit of the system), the symmetries Pna21 e Pcm21 were predetermined as common subgroups of the known space groups of the ending phases (P4mm, Pbnm, I4/mcm e Pm-3m). In turn, from the thermal expansion measurements and electric characterization, using thermal dependence of the dielectric permittivity and the polarization vs. electric field curves, some possibilities of crystallographic phase transition were determined, as well as the evaluation of the polar characteristics. To determine the tilt system and the crystal symmetry at room temperature, the electron diffraction techniques were used. The composition choice was 47.5 mol % of Ca, which represent a challenge in PCT MPB. The tilt system determined is the same of CaTiO3, the mix of antiphase and in phase tilt a-a-c+. Finally, combining results of the electron diffraction techniques set with the indirect techniques set, the orthorhombic symmetry with the point group 2mm and the space group Pna21 was found for the solid solution Pb0,525Ca0,475TiO3. This symmetry might cover other compositions in MPB at room temperatures. The results from the set of techniques protocol allowed concluding this symmetry and polar states from MPB phases as a function of temperature, adding new contribution to elucidate the PCT phase diagram.
Keywords: Cerâmicas piezoelétricas; Microscopia eletrônica de transmissão; Difração de raios X; Transição de fase ferroelétrica; Difração de elétrons por feixe convergente; Piezoelectric ceramics; Transmission electron microscopy; X-Ray diffraction; Ferroelectric phase transition; Convergent beam electron diffraction; CIENCIAS EXATAS E DA TERRA::FISICA